2021
DOI: 10.1097/hjh.0000000000002956
|View full text |Cite
|
Sign up to set email alerts
|

The association of actigraphy-assessed sleep duration with sleep blood pressure, nocturnal hypertension, and nondipping blood pressure: the coronary artery risk development in young adults (CARDIA) study

Abstract: Nocturnal hypertension and nondipping systolic blood pressure (SBP) are associated with increased cardiovascular disease (CVD) risk. Short and long sleep duration (SSD and LSD) are also associated with increased CVD risk and may be risk factors for nocturnal hypertension and nondipping SBP. We examined the association between SSD and LSD with sleep BP, nocturnal hypertension, and nondipping SBP among 647 white and African American Coronary Artery Risk Development in Young Adults (CARDIA) study participants who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…It has been argued that objective short sleep per se (SSD) but not the joint effect of objective sleep duration and insomnia is the primary condition that increases the risk of cardiometabolic diseases (Johnson et al, 2021). Our study showed that SSD was not associated with increased risk of cardiometabolic diseases, which is consistent with several previous studies (Abdalla et al, 2021; Fernandez‐Mendoza et al, 2012; Matsumoto et al, 2018; Ramos et al, 2018). Also, the Hispanic Community Health Study/Study of Latinos (HCHS/SOL) with 2252 subjects (Ramos et al, 2018) and the Nagahama study with 7051 subjects (Matsumoto et al, 2018) showed that objective SSD, defined by actigraphy, was not associated with increased risk of hypertension in the general population.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It has been argued that objective short sleep per se (SSD) but not the joint effect of objective sleep duration and insomnia is the primary condition that increases the risk of cardiometabolic diseases (Johnson et al, 2021). Our study showed that SSD was not associated with increased risk of cardiometabolic diseases, which is consistent with several previous studies (Abdalla et al, 2021; Fernandez‐Mendoza et al, 2012; Matsumoto et al, 2018; Ramos et al, 2018). Also, the Hispanic Community Health Study/Study of Latinos (HCHS/SOL) with 2252 subjects (Ramos et al, 2018) and the Nagahama study with 7051 subjects (Matsumoto et al, 2018) showed that objective SSD, defined by actigraphy, was not associated with increased risk of hypertension in the general population.…”
Section: Discussionsupporting
confidence: 93%
“…Also, the Hispanic Community Health Study/Study of Latinos (HCHS/SOL) with 2252 subjects (Ramos et al, 2018) and the Nagahama study with 7051 subjects (Matsumoto et al, 2018) showed that objective SSD, defined by actigraphy, was not associated with increased risk of hypertension in the general population. Recently, the coronary artery risk development in young adults (CARDIA) study also found that there was no evidence of an association between SSD and sleep SBP or DBP, or non‐dipping SBP, nocturnal hypertension (Abdalla et al, 2021). A modest effect of SSD, but much less potent than the effect of ISSD, has been reported in some other studies including the original study by the Penn State group (Fernandez‐Mendoza et al, 2012; Vgontzas, Liao, et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Deficits and surfeits in sleep duration (i.e. short and long sleep duration) have been postulated to be contributing risk factors to high sleep BP [1]. However, until recently, few data have been available examining the association between objectively assessed sleep duration and sleep BP.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…A s high sleep blood pressure (BP) is an independent risk factor for cardiovascular disease, it is important to identify factors that increase sleep BP in order to achieve 24 h blood pressure control. We read with great interest the article by Abdalla et al [1] that reported a positive association between long sleep duration and sleep BP. A major strength of their study was the use of a wristtype activity monitor that ensured objective measurement of sleep duration.…”
mentioning
confidence: 96%
“…132 Evidence suggests that earlier midsleep time, a proxy for sleep timing, and long sleep duration may each be associated with a higher prevalence of nondipping systolic BP. 133,134 Few findings have been published on the experimental impact of sleep restriction on BP. One study showed that repeated bouts of highly restrictive sleep (4 hour time in bed/night) increases BP relative to constant adequate sleep (8 hour time in bed/ night) and that sleep restriction reduces BP dipping relative to baseline.…”
Section: Sleep and Bpmentioning
confidence: 99%